‘AMALIYYAH TA’LIM AL SHARF FĪ AL SHAF AL AWWAL FĪ AL MADRASAH AL TARBIYAH AL ISLĀMIYYAH GONDONG - Kamaluddin, Kamaluddin; Marlion, Ferki Ahmad; Salam, Muhammad Yusuf; Amelia, Amelia (STIQ Amuntai, 2024)
This research analyzes the process of teaching morphology in the first grade at the Islamic Education School, Gondong. The School of Islamic Education, Gendonk, is one of the Islamic schools that teaches morphology. As we have seen, many of the graduates of the Islamic School of Geendunk are skilled at reading Arabic language books. Its causes are understood from the science of morphology and grammar. The end of this research is the process of teaching the grammatical teacher, not using various means and methods in all teaching morphology. The method used by the researcher in this research is the descriptive method using qualitative approaches, and the method of collecting data using qualitative descriptive methods and using observation and interview methods. As for the result of the research, all students own the blackboard themselves. Its goal is that if the students did not understand a subject in pure science, they would write on that blackboar and the teacher uses various specific methods in the process of teaching morphology, such as movies and morphology, then the card method.